2003
DOI: 10.1177/1538192702238725
|View full text |Cite
|
Sign up to set email alerts
|

School Social Context Effects on Gender Differences in Academic Achievement Among Second-Generation Latinos

Abstract: This study considers involuntary minority concentration effects on gender differences in achievement and finds increasing levels of involuntary minority enrollments decrease grade point averages and math scores for immigrant boys versus girls, net of individual and school socioeconomic status. Immigrant achievement declines in involuntary minority schools where a climate of apathy and failure inhibits performance. Yet, differences in gender roles and socialization renders girls less vulnerable to assimilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…The pattern of immigrant girls outperforming immigrant boys within the same ethnic group has been found to be consistent in smaller scale in-depth studies (Lopez, 2002;Rodriguez, 2003;Valenzuela, 1999b;Waters, 1996;Zhou & Bankston, 1994, 1998. In these different studies, researchers suggest that school plays an important role in shaping and perpetuating gender roles and racial stereotypes among immigrant students.…”
Section: Stritikus and Nguyenmentioning
confidence: 82%
See 1 more Smart Citation
“…The pattern of immigrant girls outperforming immigrant boys within the same ethnic group has been found to be consistent in smaller scale in-depth studies (Lopez, 2002;Rodriguez, 2003;Valenzuela, 1999b;Waters, 1996;Zhou & Bankston, 1994, 1998. In these different studies, researchers suggest that school plays an important role in shaping and perpetuating gender roles and racial stereotypes among immigrant students.…”
Section: Stritikus and Nguyenmentioning
confidence: 82%
“…While many immigrant families and communities embrace traditional values regarding gender roles and expectations, which tend to restrict women's personal choices and movements, studies consistently show that young immigrant women have been excelling in school (Lopez, 2002;Portes & Rumbaut, 1996Qin-Hillard, 2003;Rodriguez, 2003;C. Suarez-Orozco & SuarezOrozco, 2001;Waters, 1996;Zhou & Bankston, 2001).…”
Section: Immigrant Adjustment and Gendermentioning
confidence: 99%
“…Thus, low support may exacerbate other risks experienced by boys, while highly supportive relationships with school adults may become especially salient over time. Indeed, although some have implied that boys are less oriented toward their teachers, research has also shown that boys of Latin American descent may be more likely to be responsive to school environment factors, including the student body composition and school climate (Rodriguez, 2003). Likewise, some research shows that boys may benefit more from teacher connection and teacher caring, although they may be less likely to experience such highly supportive relationships (Furrer & Skinner, 2003;Way & Chu, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most research has typically examined individuals' social group identities in isolation from one another, often ignoring how an individual's gender and ethnic identities might interact with one another (Frable, 1997). This practice of examining group identities in a ‘social vacuum’ (Akiba et al., 2004) is especially problematic given evidence indicating that ethnic differences in parental socialization might lead to gender identity being differentially weighted within one's self‐concept depending upon one's ethnicity (e.g., Rodriguez, 2003; Valenzuela, 1999).…”
mentioning
confidence: 99%